Adaptação às mudanças climáticas em núcleos urbanos : iniciativas em cidades inteligentes e a contribuição para Agenda 2030 - Mazutti, Janaina (2021)
Climate action, expressed in the Sustainable Development Goal 13, have become essential to the urban planning. In this context, Smart Cities, often considered spaces where Information and Communication Technologies (ICTs) are applied for the efficiency of operation and services, are considered models and become important territories for the study of innovative solutions to climate change adaptation in urban areas. Therefore, the aim of this research is to investigate how the initiatives to adapt to climate change adopted in smart cities in different global contexts, contribute to the achievement of the 2030 Agenda. To do so, three methodological steps were carried out. Firstly, the identification of smart cities with reference to the report Cities in Motion Index. Following, the survey of climate change adaptation initiatives considering the three priority approaches to adaptation: increasing the adaptation capacity, reducing exposure and reducing vulnerability. Finally, the initiatives were analyzed as to their contribution to the infrastructure of cities, to the awareness of the population and to the achievement of the targets proposed by the Agenda 2030. The highlight among the initiatives is directed to Solutions Based on Nature, being massively adopted in all contexts. The most favored SDGs are SDG 9, SDG 11 and SDG 13, but each region has different priorities in relation to the other SDGs. ICT-based solutions, although not widely adopted in cities, offer innovative opportunities that can drive the future of adapting to climate change. This research innovates by promoting a new reflection for cities regarding their role in climate adaptation. The initiatives raised by the study can be understood as good practices for climate action in any municipality. Also, considering the limited scope that presents only a global view, it is up to future research to analyze the contexts in an individual and detailed way, seeking to understand how the vulnerabilities of each territory are addressed in climate adaptation.